Analisis Penilaian Kebutuhan Pengembangan Sumber Daya Manusia Di Otoritas Jasa Keuangan Needs Assessment Analysis Of Human Resources Development In Indonesia Financial Services Authority - Sancaya Naresvari Wijaya; Vishnu Juwono (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Being the only institution in Indonesia with supervisory, regulatory and audit functions in the financial services industry sector, human resources in the Indonesia Financial Services Authority (OJK) are expected to meet the quality that is in line with the dynamic development of information technology and financial innovation. Needs assessment process is required as one of the OJK's efforts to futher improve its human resources, in which there is no size or scale required for behavioral and technical competence at each role level. The purpose of this study is to analyze the needs assessment and the factors that affect the needs assessment at OJK. Current research employs a post positivism approach with qualitative methods and field study data collection techniques through in-depth interviews and literature studies. Research results reveal that the needs assessment process at OJK has not used technical and behavioral competency measures because there is no measurement referred to in the internal regulations regarding current job descriptions, therefore OJK does not yet have an accurate employee database profile.